The Implementation of Sadaqa House in Malaysia / Lubaina Syakirah Sofian Azmi - Sofian Azmi, Lubaina Syakirah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Sadaqa House is a new product by Islamic Financial Institution (IFI) in Malaysia, as an initiative of the institution to strengthen the value of Islam in economic and financial activities. The idea of Sadaqa House was proposed by Dato Dr. Abdul Halim Ismail in his speech during the Global Islamic Finance Forum 2014. The Sadaqa House Special Task Force was then established in 2017, in order to implement the idea of Sadaqa House in Islamic Banking environment in Malaysia. This study will review on: (1) the concept of sadaqah in Islam and its impact to the community, (2) the existing models of Sadaqa House and other related models such as zakat and takaful, and (3) suggestion on the appropriate model of Sadaqa House to be implemented in Malaysia. This mixed method study collected data through interview and questionnaire survey to achieve the above objectives. Based on the data from the respondents, it is found that Model A is highly selected compared to Model B and C. However, researcher tend to propose that Model C is more appropriate to be implemented in Malaysia due to few elements; 1) tax exemption given to the bank as well as donors, 2) establishment of new entity according to the depth analysis from the opinions of the practitioners in Islamic banking sector and respondents.